Projecting culture: cultural diplomacy of European states in the age of industrial imperialism (1871–1914) - Kryvashei, Dzmitry A. (Journal of the Belarusian State University. International Relations, 2022)
Industrial imperialism set the stage for the emergence of cultural diplomacy and its institutions. Departments responsible for cultural diplomacy proliferated in the foreign ministries of multiple European countries, and many colonial powers and imperial states scrambled to establish their overseas cultural institutions. Countries viewed schooling as one of their most effective instruments for the pursuit of their civilising mission. At the beginning of the 20th century, education, academic exchange and research came to the central stage of the global competition among countries for economic and political influence. Where the government was too cautious to proceed, non-government actors (organisations and individuals) filled the void. Countries relied on diplomats to steer the work of their overseas cultural institutions but used considerable discretion in doing so.
Keywords: foreign cultural policy; cultural diplomacy; industrial imperialism; cultural institutes abroad; cultural propaganda